Self-assembling dual component nanoparticles with endosomal escape capability1. Issue 15 (21st April 2015) - Wong, Adelene S. M.; Mann, Sarah K.; Czuba, Ewa; Sahut, Audrey; Liu, Haiyin; Suekama, Tiffany C.; Bickerton, Tayla; Johnston, Angus P. R.; Such, Georgina K.
<x xml:space="preserve">Abstract</x> This work reports a modular nanoparticle system engineered to undergo disassembly within a biologically relevant pH range. These nanoparticles demonstrate endosomal escape, making them attractive for biomedical applications.